Experimental evaluation of analgesic activity of PPAR γ agonists: pioglitazone and rosiglitazone - Bhamare, Chetanraj G.; Padwal, Sudhir L.; Motghare, Vijay M.; Deshpande, Rushikesh P.; Pore, Rakesh R.; Rathod, Suvarna S.; Pise, Harshal N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To evaluate analgesic activity of pioglitazone and rosiglitazone by tail flick method in rats and acetic acid induced writhing method in mice. Methods: Albino wistar rats of either sex weighing 180-200 g and Swiss mice weighing 25-30 g were used. Study was conducted after approval from the Institutional Animal Ethics Committee. The tail flick method in rats described by D’Amour and Smith (1941) and acetic acid induced writhing in mice were used. The dose of pioglitazone and rosiglitazone were 20 mg/kg and 10 mg/kg respectively. Results: In tail flick method of analgesia, both, pioglitazone and rosiglitazone have analgesic activity which was statistically comparable to aspirin. In acetic acid induced writhing model of analgesia, the action of pioglitazone and rosiglitazone was significantly greater than the control group but it was less when compared to aspirin. Conclusions: Analgesic activity of pioglitazone and rosiglitazone was comparable to aspirin in tail flick model of analgesia in rats while it was significantly less when compared to tramadol. Analgesic activity of pioglitazone and rosiglitazone was significantly less than aspirin in acetic acid induced writhing method.